Pro-Westernization Reflected In Orhan Pamuk's Istanbul Memoir (2003) : A Post-Colonial Approach - Rahmawati, Andriana, Dr. Abdilah Nugroho. M. Hum (2017)
ANDRIANA RAHMAWATI/A320120166. PRO-WESTERNIZATION REFLECTED IN ORHAN PAMUK'S ISTANBUL MEMOIR (2003): A POST-COLONIAL APPROACH. RESEARCH PAPER. DEPARTMENT ENGLISH EDUCATION MUHAMMADIYAH UNIVERSITY of SURAKARTA. SEPTEMBER, 2016 Westernization becomes a trend in many places in this world. Westernization changed many aspects in life and rule then culture that usually used in the society. One of the factors that made westernization happen is economic factor. Western culture looks so shine with their industrial that made their citizen wealth. Because of it, many countries wanted to move followed industrialization that followed with the westernization culture. Westernization came from western culture, but industrialization came to the used of machine for made handcraft changed human reproduce. Controversy happened after the successful of industrialization proved able to make the socialite wealthy than before. Many countries wanted to follow for the sufficient of their society. Till the end some country is able to pro with westernization or not. They were who are pro with westernization, we can call pro-westernization, for they that did not agree, and we can call it contrawesternization. In Istanbul memoir, they are who did not agree with westernization we can call: istanbullus or they are who still followed Istanbul rule based on Ottoman era (before westernization that populared by Turkey Republic ). Society in pro-westernization they live by western culture and style. For the example thrower television in the hall, used fireplace and the other western behavior. They did this to follow western style that spread. Pro-westernization explained in this research paper based on the Istanbul memoir by Orhan Pamuk.